Creating a Food Menu Application for Mendel University in Brno - Petr Tykal; Diana Brnovik; Jaromír Landa (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2020)
The presented paper describes the creation of a mobile application module for showing a current menu at Mendel University cafeterias. Nowadays, the students and the university staff have the menu accessible through a static webpage. The presented solution serves as a dynamic presentation of the current menu for all Mendel University in Brno cafeterias. Most cafeteria menu applications use the REST architectures for the server backend. The contribution of the paper is in usage of the Google Firebase Realtime database as a server backend. Unlike in traditional REST architecture, the data e.g. the food rating is instantaneously changed and the users have an up to date information. Part of the presented solution is also a mobile application module for both Android and iOS where university students and staff can see the current cafeterias menus.